Modelling the mode evolution and excitation in trapped single mode fiber sensor / Nurshatirah Mohamad Suhaini - Mohamad Suhaini, Nurshatirah (2017)
Fiber optic sensors have gain much interest in recent years. Optical fiber sensors such as temperature, pressure, displacement, chemical concentration, vibration and other are widely used. It can be very good sensor because of the small size, stability, no electromagnetic interference and high sensitivity.